China - winning the pandemic... for now: The People's Republic is exuding strength, but can they keep it up? - Hanns Günther Hilpert; Angela Stanzel (Stiftung Wissenschaft und Politik (SWP), 2021)
Is it not ironic that the Coronavirus pandemic, which arguably began in a Wuhan animal market in late 2019, has accelerated China's rise? Indeed, early interim assessments show that Beijing's draconian, sometimes inhumane, disease control measures have proven highly successful. China's containment of Covid-19 domestically has enabled a return to normality and laid the foundation for a strong economic upswing. Party and state leaders are using these achievements for political advancement at home and abroad. China's effective crisis management - epidemiological, economic, and political - reveal that the country is winning this crisis in the end of 2020. Nonetheless, the sustainability of these economic and political successes is debatable.
Keywords: 320